Hubungan Frekuensi Serangan Stroke dengan Tingkat Kecemasan Keluarga Stroke Survivor - Waisyaka, Anak Agung Esha; Dewi, Ni Luh Putu Thrisna; Sudarsana, I Dewa Agung Ketut (Jurnal Akademika Baiturrahim Jambi, 2025)
Recurrent stroke is one of the major challenges in patient care, affecting not only the patient’s physical condition but also the psychological well-being of their family. This study aims to analyze the relationship between the frequency of stroke attacks and the anxiety levels of stroke survivor families. This research employs a quantitative descriptive correlational design with a sample of 69 stroke survivor family members selected using purposive sampling. Data were collected using a questionnaire on stroke attack frequency and the Hamilton Anxiety Rating Scale (HARS), and analyzed using the Spearman rank test. The results indicate a significant relationship between the frequency of recurrent strokes and family anxiety levels, with a p-value < 0.001 and a correlation coefficient of 0.706, suggesting a strong positive correlation. The more frequent the stroke attacks, the higher the level of anxiety experienced by the patient’s family. Data analysis shows that the majority of families with patients experiencing their first stroke reported mild anxiety (69.6%), while those facing recurrent strokes tended to experience higher levels of anxiety. Increased anxiety is influenced by uncertainty regarding the patient's condition, financial burden, and emotional demands of caregiving. Based on these findings, it is recommended that healthcare professionals provide education on preventing recurrent strokes and stress management strategies for stroke survivor families to help reduce anxiety and improve their quality of life.